Manajemen Perubahan dalam Organisasi AMTO 147 D-13 - Nur, Mulyadi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Organizations need to think about their existence, they won't back down from changes and changes in activity. Issues related to change management activities, have appeared in the media, speeches of organizations lectures people, and academic discussions about the organization. We have witnessed a variety of changes that occur, whether the changes are less significant, and major changes that have an impact in the history of organizations and individuals in the organization. This research aims to analyze the goals of change that are organizational in nature. The results of this study show that not everyone likes or is ready for changes in the organization, but nevertheless those changes inevitably have to be faced.